The relationship of cultural intelligence and cross-cultural adjustment on expatriate job performance effectiveness: a study of Indonesian expatriates - Novia Khairunnisa (SRIWIJAYA INTERNATIONAL JOURNAL OF DYNAMIC ECONOMICS AND BUSINESS, 2023)
The research aims to determine the relationship between four-dimensional cultural intelligence and cross-cultural adjustment towards the effectiveness of Indonesian expatriates’ performance. In line with the research aim, this dissertation adopts a quantitative method by distributing questionnaires among 25-30 Indonesian expatriates who work at multinational corporations in the United Kingdom. The finding demonstrates a significant relationship between motivational and cross-cultural adjustment and expatriate performance effectiveness. Additionally, this research claims that most expatriates received no training prior to departing. In implication, managers are recommended to be more receptive to expatriates in terms of helping them assimilate to local culture rapidly and accordingly. Also, further research should investigate gender effect as a moderator between four-dimensional Cultural Intelligence (CQ) to Cross Cultural Adjustment (CCA), which may affect their job performances.